A 10-year Review of TB Notifications and Mortality Trends Using a Joint Point Analysis in Zambia - a High TB burden country. (November 2022) - Lungu, Patrick; Kasapo, Clara; Mihova, Reford; Chimzizi, Rhehab; Sikazwe, Lyapa; Banda, Isaac; Mucheleng'anga, Luchenga Adam; Chanda-Kapata, Pascalina; Kapata, Nathan; Zumla, Alimuddin; Mwaba, Peter
Highlights: From 2018 to 2020, Zambia recorded an increase in TB notifications in the patients ages 45 and above An increase in drug resistant TB cases detected by GeneXpert MTB/RIF were seen Bacteriologically confirmed TB cases were more than the clinically diagnosed. Negative growth in case detection of childhood TB Abstract: Background: Zambia is one of the TB high-burden countries. It is important to track the progress being made towards enhancing case finding and reducing mortality. We reviewed routine TB notifications and mortality trends, over a decade from all facilities in Zambia. Methods: A 10-year retrospective study of TB notifications and mortality trends was performed using a Joint Point Analysis version 4.9.0.0, NCI. We extracted the annual national TB program data for the period under review. Results: There was a decline in annual point average for notification between 2010 and 2020 in both males and females, but the females notification rates had a higher rate of decline (AAPC = -6.7, 95%CI:-8.3 to -5.0), p<0.001) compared to the decline in males notification rate (AAPC = -4.1, 95%CI:-4.1 to -5.1, P<0.001). We found a significant growth rate in the proportion of TB patients that were bacteriologically confirmed (AAPC = 6.1, 95% CI: 3.6 to 8.7, p< 0.001), while the proportion of clinically diagnosed patients declined (AAPC= -0.1, 95%CI: -2.3 to 2.1, p<0.001). Notification of drug-resistant TB increased exponentially (AAPC=27.3, 95% CI: 13 to 41), p< 0.001) while mortality rate declined from 21.3 in 2011 to 12.7 in 2019 per 100, 000 population (AAP=-5.6, 95%CI: -9.6 to -1.5, p=0.008). Conclusions: This study has illustrated the importance of reviewing and analyzing routinely collected TB data by national programs. The study revealed areas of improvement in terms of TB control and underscores the need for increased and sustained investment in case detection and diagnostics.